The Influence of Customer Relationship Management (CRM) and Customer Satisfaction on Sales Increase Through The Use of Digital Services at PT PLN (Persero) UP3 Ogan Ilir - Hayani , Eko Saputra; Wadud, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the influence of three main variables: Customer Relationship Management (CRM), customer satisfaction, and sales improvement of electricity through the Digital Service PLN at PT PLN (Persero) UP3 Ogan Ilir. A quantitative approach was applied using a survey method, with questionnaires distributed to 100 active users of the PLN Mobile application. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The model includes two independent variables CRM and customer satisfaction and one dependent variable, namely sales improvement. The results show that CRM has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction significantly affects sales improvement. CRM also has an indirect influence on sales improvement through customer satisfaction as a mediating variable. These findings suggest that effective CRM implementation enhances customer satisfaction, which ultimately contributes to increased electricity sales through digital service channels. The study recommends that PT PLN (Persero) continuously strengthen CRM strategies and prioritize customer satisfaction to support the utilization of PLN Mobile and sales performance. Keywords: Work-Life Balance, Non-Physical Work Environment, Job Satisfaction.